Optimalisasi Pemasaran Digital melalui Website Terintegrasi dalam Meningkatkan Ekonomi dan Daya Saing UMKM Dejarumi - Muhammad Eka Purbaya; Chusnul Maulidina Hidayat; Silvia Van Marsally; Paradise Paradise (BADAN PENERBIT STIEPARI PRESS, 2025)
The development of digital technology provides great opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand market reach and increase competitiveness. MSME Dejarumi, as one of the local business groups, still faces various obstacles in terms of marketing and optimal use of digital technology. This community service activity aims to support the increase in the capacity of MSME Dejarumi through optimization of digital marketing based on an integrated website. The implementation method includes needs analysis, integrated website development, digital marketing training and assistance, assistance and monitoring, as well as program evaluation and improvement. The results of the activity show that the existence of an integrated website can increase product visibility, simplify the transaction process, and expand market access. In addition, MSME actors also experienced an increase in understanding and skills in managing digital marketing independently. Thus, this program has succeeded in encouraging the sustainable improvement of the economy and competitiveness of MSME Dejarumi through targeted digital transformation.